CCL2 expression is mediated by type I IFN receptor and recruits NK and T cells to the lung during MVA infection. Issue 6 (18th March 2016) - Lehmann, Michael H; Torres-Domínguez, Lino E; Price, Philip J R; Brandmüller, Christine; Kirschning, Carsten J; Sutter, Gerd
Abstract : MVA-induced CCL2 expression and recruitment of leukocytes in mice is mediated by IFNAR1, but not TLR2. Abstract: Migration of leukocytes to the site of microbial infection is important for the development of effective host immunity. Recombinant modified vaccinia virus Ankara is frequently used as a viral vector vaccine in preclinical and clinical studies. In comparison to other vaccinia virus strains, modified vaccinia virus Ankara robustly induces chemokine expression and rapid attraction of leukocytes. In particular, chemokine (C-C motif) ligand 2 (CCL2) has been shown to be critical for leukocyte recruitment to the lung. In this study, MVA-induced CCL2 expression in murine macrophages was dependent on type I interferon receptor and not Toll-like receptor-2. The critical role of type I interferon receptor signaling for CCL2 production in the lung was confirmed in type I interferon receptor–deficient mice ( Ifnar1 −/− ). In addition, comparing Ifnar1 −/− and Ccl2 −/− mice with wild-type mice, we observed a similar impairment in the recruitment of natural killer and T cells to the lung after intranasal infection with modified vaccinia virus Ankara. Conversely, neutrophil recruitment was not affected in Ifnar1 −/− and Ccl2 −/− mice. We conclude that type I interferons, besides their known antiviral properties, can initiate the recruitment and activation of leukocytes via induction of chemokine expression including CCL2.